My dad - Browne, Anthony, 1946- (New York : Farrar, Straus, Giroux, 2001)
A child describes the many wonderful things about "my dad," who can jump over the moon, swim like a fish, and be as warm as toast.
"First published in Great Britain by Doubleday ... 2000"--T.p. verso.
Book Links (A.L.A.).
School Library Journal starred.
Wilson's Children.
1.3.
1.3
Keywords: Fathers -- Fiction; Fathers -- Fiction